DISCRIMINANT ANALYSIS APPLIED TO PREDICTION MODELS IN BANKRUPTCY - Aldazábal Contreras, Janet Cecibel (2014)
The companies increasingly interact with clients and providers. This situation requires adequate risk ma-nagement to prevent situations of financial distress. A company is technically insolvent when it has enough cash to make immediate payments. Therefore, one of the points to study is the financial solvency and risk to the bankruptcy of its customer base. To this end, there are techniques to measure the possibility of insolvency of a company. The most reliable is the Altman Z model, which is based on the statistical technique of Multiple Discriminant Analysis. This model uses financial ratios to determine the financial risk and predict whether a company is healthy from a financial point of view, or is on its way to become insolvent. The results found by Altman and revision of the original model proposed by him is presented.